Comparison of Social Participation Level Between Older Adults With Assistive Mobility Devices and Those Without the Devices - Karim Ayoubi Avaz; Shahriar Parvaneh; Ahmad Ali Akbari Kamrani; William Miller; Pouria Reza Soltani; Setareh Ghahari (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: Social participation is an important aspect of health in ageing. It is also a part of life and a key element in function that improves physical and psychological health in the elderly. Using assistive mobility devices may influence social participation in this population. Current study aimed to compare social participation in older adults who use assistive mobility devices with those who do not use assistive devices in Tehran. Methods & Materials: In this cross-sectional study, older adults with and without assistive mobility devices were comprised in their social participation. Seventy-nine old age adults (39 women and 40 men) who were 60 years or older were recruited using convenience sampling method. They completed life habit, mini mental state and demographic questionnaires. For analyzing continuous data with normal distribution, t test and ANOVA were used, while Kruskal-Wallis and Mann-Whitney tests were used for categorical variables or those with non-normal distribution. Results: The finding indicates that older adults with assistive mobility devices engage less in social participation than those who do not use these devices (P<0.05). Older adults in age group of 60-74 years had higher social participation in comparison with those in 75-89 age group (P<0.05). There was no significant differences between male and females, and single older adults and married ones in their social participation. Conclusion: Type of assistive device affects social participation in older adults. The results suggest that older adults with higher physical ability have higher social participation. Older adults who use assistive devices face with more limitations to participate socially in their community. It is necessary for rehabilitation team to pay attention in improving social participation of older adults.